SIGNIFICANCE OF P53 AND BCL-2 GENES IN CERVICAL CANCER. - Farrukh Sh. Fayziev (Scholar Express Journals, 2023)
Literature data on the effect of the amount of apoptosis and the apoptosis index on the prognosis of malignant tumors are contradictory. Theoretically, active apoptosis in a tumor means its slow growth and low aggressiveness. In addition, the action of many antitumor agents is mediated by the induction of apoptosis.
Keywords: Cervical cancer; endometrial cancer; P53 and BCL-2 genes